Health education as a strategy to promote the development of the prematurely born child: perception of caregivers - Rena, Pamela Brustolini Oliveira; Henriques, Bruno David; Lemos, Rayla Amaral; Veríssimo, Maria De La Ó Ramallo; Morelo, Jamile Gregorio; Moreira, Tiago Ricardo; Oliveira, Deíse Moura de (Ciência e Natura, 2022)
The birth of a premature baby can cause impairment in the child’s development, requiring a critical analysis from the health professional of their performance in the care directed to this public and their family. There is lack of scientific literature focused on the promotion of functional development of premature infants, making necessary the use of technologies that help the family in home care. Objective: To understand the knowledge and practices of caregivers of prematurely children, about the functional development mediated by an intervention with an educational technology. This was a qualitative, descriptive, exploratory and intervention research, with 11 mothers of prematurely born children, followed up by a service in a city of Minas Gerais. Performed in three steps. The first still in the follow up service, the second and third consisted of home visits. The analysis originated the categories “Expectations related to the educational material”, “Experiences with the educational material” and “Changes in care aroused by the appropriation of the educational material”. The work of the health educator articulated with an educational technology focused on promoting the child development of premature children contributes to the resignification of knowledge and everyday practices of care directed to this public.